Response of Bird Community to Kamojang Geothermal Power Plant, Bandung, West Java - Diyah Kartikasari; Satyawan Pudyatmoko; Novianto Bambang Wawandono; Pri Utami (Jurnal Ilmu Kehutanan)
This study aimed to investigate the response of bird communities on the presence of geothermal power plant of Kamojang. We compared the bird diversity and richness of affected (DL) and not affected (TL) in Kamojang Geothermal Working Area, Kamojang Nature Reserve and Kamojang Nature Park in Bandung regency of West Java Province. The affected sites were surrounding production wells or geothermal power plants (30 samples) whereas not affected sites were with distance of 3,000 m to 9,000 m from those facilities (42 samples). The data collection was carried out during two seasons; dry and rainy season in (2015-2016). In each site, we collected bird community data and habitat data with the point count method which was placed systematically on each sites. We found 124 birds species belongs to 35 families with 16 endemic species in Java Island. Twenty three species are protected by Indonesian law, with nine species are in the CITES appendix list and five species are listed in the IUCN Red List of Threatened Species of 2017. There was a difference of responses between bird communities in the affected and not affected sites which is indicated by differences in the mean number of species, number of individuals in each species, and Shannon-Wiener's diversity index. The not affected sites had higher value on these parameters than the affected sites. Similarly, number of species, number of individual vegetation, and Shannon-Wiener biodiversity index in TL sites had higher mean values than DL sites. This proves that although geothermal is considered as environmentally friendly energy but in its utilization it still has an impact on the surrounding biodiversity especially for bird species.